Investigation of Defects in Cs2SnI6‐Based Double Perovskite Solar Cells Via SCAPS‐1D. Issue 9 (13th July 2022) - Porwal, Shivam; Paul, Mrittika; Dixit, Himanshu; Mishra, Snehangshu; Singh, Trilok
Abstract: Effective conversion of solar photons into electrical power through the development of smart and eco‐friendly materials is one of the most extensively researched methods for generating renewable energy. In this work, an inorganic lead‐free double perovskite Cs2 SnI6 material is employed as an active layer for solar cell applications, together with GO (graphene oxide) as electron transport layer (ETL) and Cu2 O as hole transport layer (HTL). In order to find the most efficient photovoltaic device, a detailed theoretical study using the SCAPS‐1D simulation program is conducted. The device performance is monitored and analyzed by considering various HTLs, doping density in active layer, light intensity, ETL thickness, operating temperature, parasitic resistances, and the role of defects on device performance. The optimized device displays a power conversion efficiency of 23.64% with excellent photovoltaic characteristics. This theoretical study reveals that Cs2 SnI6 can be a promising choice for solar cell applications as a lead‐free double perovskite material. Abstract : Inorganic lead‐free double perovskite Cs2 SnI6 material is employed as an active layer for solar cell applications and the combination of GO (graphene oxide) as electron transport layer (ETL) and Cu2 O as hole transport layer (HTL) shows best device characteristics with power conversion efficiency of 23.64%.